Changes in Athletic Fitness of Junior Sports Dancers During a Ten-Month Training Cycle - Aistė Barbora Ušpurienė; Algirdas Čepulėnas (Lithuanian Sports University, 2018)
Research background and hypothesis. Research shows that the mastery level of dancers in sports dancing is closely related to their athletic fitness though there has not been enough research in the changes of indices of athletic fitness of junior sports dancers while training sports dancing. The present study aims at verifying the hypothesis that training in sports dancing should improve athletic fitness of sports dancers. Research aim was to test the effect of training in sports dancing on the indices of athletic fitness of junior sports dancers. Research methods. The subjects in the research were 14 junior sports dancers: 7 girls and 7 boys. The dancers were tested twice: in January 2010 and in November 2010. The training sessions were held three times a week. We established the following indices of athletic fitness: hand grip strength, the frequency of fine hand movements, the frequency of leg movement running on the spot for 10 s, speed of hand movements performing 25 cycles of movements, static balance, trunk flexibility, dynamic strength endurance of abdominal muscles, explosive strength and speed strength of legs, explosive strength endurance, simple and complex psychomotor reaction to light stimulus. Research results. Dancing practice sessions had a positive effect on psychomotor abilities of boys and girls - simple psychomotor reaction for girls (p < 0.05) and simple and complex psychomotor reaction for boys (p < 0.05). The indices of athletic fitness of junior sports dancers did not change much in the research period. Discussion  and  conclusions.  Specialized  dancing  practice  sessions  did  not  have  significant  effect  on  the improvement  of  athletic  fitness,  however,  a  tendency  of  improvement  in  athletic  fitness  was  observed. Athletic fitness is a significant component of junior sports dancers' sports fitness, and the improvement of athletic fitness indices requires inclusion of athletic training into the programs of training sports dancers, or regular practice sessions in sports dancing should be supplemented with physical exercises for the development of motor skills. Keywords: sports dances, athletic training, motor skills, dancing practice sessions, training.